RELATIONSHIP BETWEEN THE MEATABOLIC SYNDROME AND THE INDIVIDUAL METABOLIC RISCK FACTORS AND SYMPTOMATIC AND ASYMPTOMATIC CAROTID ARTERY DISEASE: IS THE WHOLE LARGER THAN ITS PARTS - Deleva Stoshevska, Tatjana; Nikoloska, Sofija; Stoshevski, Bojan; Nikoloski, Marko; Veljanovski, Dimitar (Journal of Morphological Sciences; Vol 4 No 2 (2021): JMS, 2021)
Metabolic syndrome (MetS) is a group of at least three of the following metabolic risk factors : central obesity, elevated glycaemia, high serum triglycerides, low serum high-density lipoprotein (HDL), and high blood pressure. Atherosclerosis is the most common cause of extracranial CAD. It may be asymptomatic and symptomatic with clinical presentation of cerebrovascular insult (CVI) and transient ischemic attack (TIA).  Aim: to determine the relationship between MetS as a whole compared to individual metabolic risk factors and CAD. This analytical unicentric cross-sectional study included 160 subjects divided into two groups: 80 subjects with MetS according to the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) criteria in the examined group (EG) and 80 subjects who have 1 or 2 individual metabolic risk factors and do not meet the diagnostic criteria for MetS in the control group (CG). CAD was diagnosed with the Esaote My Lab70 HVG device, with a linear probe (7.5 MHz), according to the Ultrasound consensus criteria for CAD of the Association of Radiologists (2002, San Francisco).  CAD was significantly more frequently diagnosed in 77 (96.25%) EG subjects, compared to 34 (42.5%) CG subjects (p <0.0001). In EG symptomatic CAD had 52 subjects (67.5%) compared to only 2 (5.9%) subjects in CG. With asymptomatic CAD were 25 (32.47%) EG and 32 (94.12%) CG subjects, which was statistically confirmed as significant (p <0.0001).  MetS is significantly associated with CAD, which is of cardinal importance for primary and secondary prevention of CVI and TIA. Keywords : metabolic syndrome, carotid artery disease, cerebrovascular insult, transient ischemic attack https://doi.org/10.55302/JMS21421113ds